Desain Motor Kapasitor Dua Fasa Simetris 1 kW - Hariz Santoso, Asfari; Ananto, Rhezal Agung; Hermawan, Ahmad; Dali, Sri Wahyuni (Elposys: Jurnal Sistem Kelistrikan, 2024)
Single phase induction motors are one of the most frequently used types of motors because of their economical, sturdy, simple and easy maintenance advantages. One application is for electric vehicles. When single phase induction motors are applied to electric vehicles there are problems related to torque regulation based on vehicle operating conditions where when operating on light road conditions the torque produced by the motor remains high. In this research, a single-phase induction motor was made to have the same proportion of torque produced by the main coil and auxiliary coil or a 1kW 1000 rpm symmetrical two-phase induction motor. The type of winding applied to the stator is divided screws with the main and auxiliary coils each occupying 18 stator slots, 45 conductors per slots,, with a conductor diameter of 1.2 mm. As a phase shifter at start and operation so that they differ by 90°, a capacitance of 505.51 µF is used. As a result of the winding modification, the induction motor parameter values ​​for each stator winding are the same. So the starting torque of the main and auxiliary coils is 3.89 Nm and 3.88 Nm respectively and the nominal torque produced by the main and auxiliary coils is 4.28 Nm and 4.29 Nm respectively.